Hak Kebebasan Berserikat Bagi Pekerja Sebagai Hak Konstitusional - Budiono, Abdul Rachmad (Mahkamah Konstitusi Republik Indonesia, 2016)
Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia guarantees the right of everyone to freedom of association, assembly, and to express opinions. Thus, the right of workers or labours to freedom of association is guaranteed by the Constitution. The principle which is embedded in the 1945 Constitution has been incorporated into Law Number 21 Year 2000 concerning Labour Union. The substance of the rights to freedom of association aims to give bargaining power to workers represented by the union against employers. The bargaining position of labour unions is expected to improve the functioning of the unions to defend the interest of workers.